Does Organizational Culture Capability and Relationship Building Capability expediate Supply Chain Operational Performance? Evidence from Indonesia - Obsatar Sinaga; Nova Indah Saragih; Rima Rachmawati; Omar Alaeddin (International Journal of Supply Chain Management, 2019)
The current study considered the effect of organization culture capability and relationship building capability on supply chain operational performance with the mediating role of supply chain technology adoption. This study focused on the Indonesian supply chain companies. Data were collected from the employees of supply chain companies. Questionnaires were distributed with the help of area cluster sampling techniques and 7-point Likert scale was preferred. Total 350 questionnaires were distributed with the help of email. Data were analysed with the help of Partial Least Square (PLS). Results of the study investigated that organization culture capability and relationship building capability both have an important contribution in supply chain operational performance through supply chain technology adoption. Moreover, supply chain technology adoption playing a mediating role. Thus, majorly this study contributed by highlighting the mediating role of supply chain technology adoption.